2023
DOI: 10.3390/fermentation9020171
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pigments under Submerged Culture through Repeated Batch Fermentation of Immobilized Talaromyces atroroseus GH2

Abstract: Pigments of natural origin have become a research trend, and fungi provide a readily available alternative source. Moreover, developing novel processes that increase yields, reduce process time and simplify downstream processing is of increased interest. In this sense, this work proposes an alternative for Talaromyces atroroseus GH2 biomass re-utilization to produce pigments through consecutive batches using immobilized mycelium. Different support materials were evaluated for pigment production and immobilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Remarkably, T. atroroseus, which happens to be the nearest relative to T. albobiverticillius, is renowned for its ability to produce monascus pigments, which are highly applicable in the food industry [37]. A draft genome of a prospective fungal cell factory, T. atroroseus IBT 11181 (CBS 123796), was reported in 2017 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, T. atroroseus, which happens to be the nearest relative to T. albobiverticillius, is renowned for its ability to produce monascus pigments, which are highly applicable in the food industry [37]. A draft genome of a prospective fungal cell factory, T. atroroseus IBT 11181 (CBS 123796), was reported in 2017 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, immobilized cell fermentation has been viewed as a promising biotechnological tool and provides an efficient approach in terms of productivity, stability, extraction, and process control. Ruiz-Sánchez et al [9] with immobilized cells of T. atroroseus GH2 using different support material to produce red pigments. The authors reported that at improved conditions, pigment production was 30% higher than using free cells, accompanied by a long-lasting immobilization activity (99.01 ± 0.37%).…”
mentioning
confidence: 99%